Bicultural responsiveness in Aotearoa New Zealand : an immigrant counsellor's perspective : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Education, Te Kupenga o te Mātauranga, Aotearoa New Zealand - Lang, Stephen Kenneth Wilfred; Lang, Stephen Kenneth Wilfred (Massey University, 2011)
This thesis examines my response, as an immigrant counsellor, counsellor educator, and member of a counsellors’ professional association, to the call by Māori for counsellors to honour and respect the indigenous culture and Te Tiriti O Waitangi, by developing bicultural responsiveness. Applying an autoethnographic critical research methodology I chart the shifts in my epistemology, ontology, and axiology, over the duration of this research. In this way I observe my own struggles to change my ‘ways of being’, by blending my academic, poetic and journal writing. Central to the dissertation are three articles published during the course of my doctoral research, which analyse the (re)formation of a counsellors’ professional association as a biculturally responsive organisation; the task of finding ‘common spaces’ that privilege cross-cultural ethics; and the use of Noho Marae in the (re)education of counsellors. The research produced a shift in the researcher’s view of himself from being Pākehā to Tauiwi, and this change altered his perception of biculturalism and the Treaty of Waitangi. The autoethnographic research method was most suited to the task of in-depth personal analysis; and there emerged a view that the struggle to adopt counselling practices that are biculturally responsive, though difficult to achieve and prone to recidivism and regression, develops alongside the shift in an individual’s worldview and cultural identity. Non-Māori of all cultures need to collaborate with Māori, and in a three stage sequence, acknowledge our mistakes, make amends, and become wiser in the process. This thesis argues that, among other initiatives, the proposal by the counsellors’ association for bicultural consultation to become mandatory will assist with this development of bicultural responsiveness through increased opportunities for interaction and dialogue. This will create ways of deconstructing dualism and advantaging holistic views of health by reintegrating all aspects of well being; as envisioned by the concept of Hauora.
Keywords: Biculturalism; Cross-cultural ethics; Cross-cultural counselling